INDUKSI PERAKARAN NILAM (Pogostemon cablin Benth) MELALUI PEMBERIAN ZPT IBA (Indol Butyric Acid) - Kamsia Dorliana Sitanggang (JURNAL AGROPLASMA, 2019)
Patchouli (PogostemoncablinBenth) is a plant that has been known to take oil extraction. One of the patchouli propagation techniques is cuttings. This research aims to get the best consentration of induced of Patchouli root. The research was conducted in STIPER Labuhanbatufrom January 2017 to June 2017. The plant material was Patchouli at the cuttings with a bud. The results showed that the best concentration to obtain a high percentage of life (90%), root length (22.27 cm) and the highest number of roots (5.03 units) in patchouli plants was treated with a 25 ppm IBA immersion. Keywords: bud, cuttings, extraction, propagation